2017
DOI: 10.1128/aac.00454-17
|View full text |Cite
|
Sign up to set email alerts
|

NDM-5 and OXA-181 Beta-Lactamases, a Significant Threat Continues To Spread in the Americas

Abstract: Among Gram-negative bacteria, carbapenem-resistant infections pose a serious and life-threatening challenge. Here, the CRACKLE network reports a sentinel detection and characterization of a carbapenem-resistant Klebsiella pneumoniae ST147 isolate harboring bla NDM-5 and bla OXA-181 from a young man who underwent abdominal surgery in India. bla NDM-5 was located on an IncFII plasmid of Ϸ90 kb, whereas bla OXA-181 was chromosomally encoded. Resistome and genome analysis demonstrated multiple copies of the transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 33 publications
2
53
3
Order By: Relevance
“…Although NDM-5-producing strains are not as widespread as NDM-1-producing strains, they can also accompany multiple resistance gene determinants of resistance to different antimicrobials in the same strain, which makes them a potential public health threat. Furthermore, bla NDM-5 can occasionally occur simultaneously with bla OXA-181 (20)(21)(22), but bla OXA-181 was not found in our study. The NDM-5-producing strains described in our study showed high resistance to all ␤-lactams and inhibitors.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Although NDM-5-producing strains are not as widespread as NDM-1-producing strains, they can also accompany multiple resistance gene determinants of resistance to different antimicrobials in the same strain, which makes them a potential public health threat. Furthermore, bla NDM-5 can occasionally occur simultaneously with bla OXA-181 (20)(21)(22), but bla OXA-181 was not found in our study. The NDM-5-producing strains described in our study showed high resistance to all ␤-lactams and inhibitors.…”
Section: Discussioncontrasting
confidence: 85%
“…Sixteen K. pneumoniae isolates carrying bla NDM-5 in our study belonged to the same sequence type, ST48, and had similar PFGE profiles, strongly indicating that clonal dissemination of K. pneumoniae carrying bla NDM-5 had occurred in our hospital. To our knowledge, bla NDM-5 -positive K. pneumoniae isolated from clinical samples has been identified in ST2250 in China (7), ST2266 in New Zealand (26), ST147 in the United States (21), and ST231 in Singapore (22) and in untypeable isolates in India (18). This is very possibly the first report in the world of ST48 carbapenem-resistant K. pneumoniae carrying the bla NDM-5 gene.…”
Section: Discussionmentioning
confidence: 66%
“…To our knowledge, this is the first report describing clinical isolates of K. pneumoniae co-harboring genes encoding NDM-5 and OXA-232. Strains of K. pneumoniae co-producing NDM-5 and OXA-181 were isolated in Singapore in 2013 (Balm et al, 2013), South Korea in 2015 (Cho et al, 2015), the United Arab Emirates (Sonnevend et al, 2017), the United States (Rojas et al, 2017and Egypt in 2019(Soliman et al, 2019. In addition, a K. pneumoniae strain co-producing NDM-1 and OXA-181 was reported in 2013 in Singapore (Balm et al, 2013), and a strain co-producing NDM-7 and OXA-181 was reported in 2015 in Denmark (Hammerum et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the plasmid harboring the mcr gene in K. pneumoniae was similar to other IncHI2-type plasmids present in E. coli, and upstream of the mcr gene was the common ISApl1 transposon. NDM-5 has been reported in many other countries, including India [19], China [20], Denmark [21], Italy [22], America [23], and Spain [24]; it has also been isolated from pigs [25,26], dairy cows [27], and vegetables [28]. In the present study, the IncX3 plasmids harboring bla NDM−5 were highly similar in various sources, suggesting their ability to be an e cient vehicle for bla NDM−5 dissemination among humans, animals, food, and the environment via the human intestine.…”
Section: Discussionmentioning
confidence: 99%